2017
DOI: 10.1093/cid/cix507
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma hominis Infections Transmitted Through Amniotic Tissue Product

Abstract: Mycoplasma hominis was transmitted through amniotic tissue from a single donor to 2 recipients. Current routine donor screening and product testing does not detect all potential pathogens. Clinicians should be aware that M. hominis can cause surgical site infections, and may not be detected by routine clinical cultures. The lack of a standardized system to track tissue products in healthcare facilities limits the ability of public health agencies to respond to outbreaks and investigate other adverse events ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Mycoplasma hominis: Twenty M. hominis clinical strains were originally obtained from Shanghai Corps Hospital of Chinese People’s Armed Police between 2013 and 2018 and stored in the strain bank at the Institute of Antibiotics, Huashan Hospital at –80°C. M. hominis culturing was performed as described previously (Novosad et al, 2017). All strains were identified by colony morphology.…”
Section: Methodsmentioning
confidence: 99%
“…Mycoplasma hominis: Twenty M. hominis clinical strains were originally obtained from Shanghai Corps Hospital of Chinese People’s Armed Police between 2013 and 2018 and stored in the strain bank at the Institute of Antibiotics, Huashan Hospital at –80°C. M. hominis culturing was performed as described previously (Novosad et al, 2017). All strains were identified by colony morphology.…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigations have documented challenges in tracing tissue products from donors to recipients in the USA. 29 , 30 Here, product tracing was only accomplished through voluntary and resource-intensive efforts, which included cooperation from the product manufacturer and distributor; collaboration between federal, state, and local health officials; and voluntary product tracking by the affected health-care facilities. However, identification of tuberculosis in a patient who received a bone allograft from a different donor highlights ongoing limitations in the ability to trace tissues from donor to recipient.…”
Section: Discussionmentioning
confidence: 99%
“…WGS analysis between the donor tissue and one of the patient isolates showed that the isolates were identical. 31 While WGS has proven to be a useful tool in cluster-outbreak and donor-transmission investigations, it can also be used to predict antimicrobial susceptibilities by detection of resistance genes. 29 The presence of the tetM gene confers tetracycline resistance in M. hominis, and prior studies have shown concordance between the biochemical susceptibility testing and detection of the specific gene.…”
Section: Discussionmentioning
confidence: 99%
“…described four patients with M. hominis spinal surgical site infections after receiving amniotic tissue product recovered from the same donor. WGS analysis between the donor tissue and one of the patient isolates showed that the isolates were identical 31 …”
Section: Discussionmentioning
confidence: 99%